2016
DOI: 10.1159/000441741
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease in Time Covering Eradication for All Patients Infected with <b><i>Helicobacter pylori</i></b> in Japan

Abstract: Background: The prevalence of gastroesophageal reflux disease (GERD) has increased in Japan since the end of the 20th century due to changes in environmental factors, such as a decreased infection rate of Helicobacter pylori and increased ability of acid secretion in the Japanese population. In 2013, the Japanese health insurance system started to cover eradication treatment for all patients infected with H. pylori to prevent gastric cancer, suggesting we may soon be able to completely eradicate this infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Furthermore, the Japanese evidence-based clinical practice guideline for FD strongly recommends the use of H. pylori eradication therapy due to a high evidence level [4]. However, the relationship between H. pylori eradication therapy and the development of gastroesophageal reflux disease (GERD) remains controversial [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Japanese evidence-based clinical practice guideline for FD strongly recommends the use of H. pylori eradication therapy due to a high evidence level [4]. However, the relationship between H. pylori eradication therapy and the development of gastroesophageal reflux disease (GERD) remains controversial [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies indicated that reflux esophagitis was developed following eradication therapy [4, 15], recent studies in Japan have indicated that the frequency or severity of this esophagitis, evaluated by endoscopy, was not serious [16–20]. Evaluation of reflux symptoms after eradication can be difficult, and one study in Japan suggested that the reflux symptoms might be improved and/or not exacerbated after eradication [21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the hygienic environment in Japan has markedly improved [12]. Although the incidence of H. pylori infection in individuals 50 years old or older exceeds 50%, the incidence of H. pylori infection in younger individuals is progressively lower with increasing age.…”
Section: Reasons For the Increase In The Incidence Of Barrett's Esophmentioning
confidence: 99%